Implicações do (des)alinhamento entre estratégia competitiva e competências financeiras organizacionais - Pinheiro, Jandira Pazzini (2012)
Based on the increase in competition and the need for new management tools to enable companies creating and sustaining competitive advantages and considering that financial management is an important activity for all organizations, this study aimed to uncover the implications of the alignment or non-alignment between competitive strategy and financial competencies. In this study, the literature about the concepts and theories was investigated in order to bring them up to date and find other studies that could contribute to this research. Six companies participated in this multiple case study, featured as a qualitative manner; although some quantitative data were used to identify the existence or non-existence of the alignment. The data were collected using a questionnaire applied by the researcher and using a four question based interview, besides the search for information on the companies websites. The treatment and data interpretation used descriptive statistics and focused on content analysis technique. The results first pointed to the benefits that an integrated alignment between competitive strategy and financial competencies can offer to a firm by building an alignment model. Nevertheless, it was found that most companies (among those that were studied) did not present a satisfactory alignment between competitive strategy and financial competencies as well as some studies realized in other managerial areas developed before this one (Corneta, 2008 and Zagui, 2010). By the end of the study, it was noticed that one important block to the alignment implementation process is the unawareness or misunderstanding about the concept of financial competencies and the non-clarification and/or lack of internal communication about the competitive strategy adopted. This implicates that companies that do not focus on the distinctive activities, which are able to guarantee competitive strategy reaching, are probably wasting resources (material, human and financial).